Composite current collector for negative electrode of lithium ion secondary battery, preparation method and equipment thereof

By using aramid fiber aggregate and a composite fluid of conductive carbohydrate slurry made of electrospinning in lithium-ion secondary batteries, the problems of low conductivity and insufficient safety in the prior art are solved, and the battery is realized The energy density and cycle life are improved, while enhancing the safety performance of the battery.

CN119297291APending Publication Date: 2025-01-10DALIAN CBAK POWER BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411698909.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

The existing composite liquid collectors have problems such as low conductivity, heat resistance and insufficient mechanical strength in lithium-ion secondary batteries, resulting in poor battery safety.

Method used

Polyterephthalyl terephthalyl phenylenediamine (Kevla) is electrospinned into an aramid fiber aggregate, with a porosity controlled between 10-90%, and a conductive carbohydrate slurry is coated thereon and passed The pressurized molding process produces a composite current collector, which is used as the negative current collector of lithium-ion secondary battery, and combines conductive agents such as acetylene black, carbon black, VGCF, carbon nanotubes, graphene, and binders such as CMC carboxymethylcellulose sodium , PAA, dispersants such as polyvinylpyrrolidone, etc. form conductive paste and are rolled into molding by heat rollers.

Benefits of technology

It improves the battery energy density, reduces the battery internal resistance, improves the battery rate performance and cycle life, and significantly improves the battery safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119297291A_ABST
    Figure CN119297291A_ABST
Patent Text Reader

Abstract

The invention discloses a composite current collector for a negative electrode of a lithium ion secondary battery as well as a preparation method and equipment thereof, and provides the following scheme aiming at the problems that the surface of an existing pure copper foil is easily oxidized to form copper oxide and the conductivity is relatively poor. The preparation method of the composite current collector for the negative electrode of the lithium ion secondary battery comprises the following steps: pouring a conductive agent, a binding agent and a dispersing agent into a 200L V-shaped mixer for dry mixing for 30-60 minutes according to the mass ratio of (90-99): (0.3-3): (0.2-5), and mixing to obtain a mixture; the mixed material is transferred to a 600L slurry mixing tank, solvent water is uniformly added in three times, after water is added each time, the speed of a stirring paddle is controlled to be 10-40 r / min, the speed of a dispersion coil is controlled to be 50-100 m / s, and the operation time is 30-60 min. Compared with a traditional cell, the cell prepared by adopting the composite current collector prepared by the invention as the negative electrode current collector of the lithium ion secondary battery has the advantages that the performance of the cell is improved, and the service life of the cell is prolonged. The energy density of the battery is improved by 3-8%; the internal resistance of the battery is reduced by 5-12%, and the cycle life of the battery is prolonged; and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a composite current collector for a negative electrode of a lithium ion secondary battery, a preparation method and equipment thereof. Background Art

[0002] The current collector plays a vital role in lithium batteries. It connects the powdered active materials by coating. On the one hand, it collects and outputs the current generated by the active materials, and on the other hand, it inputs the electrode current to the active materials. Usually, the negative electrode of the lithium battery current collector is made of copper foil.

[0003] As one of the important technical paths in the future battery field, the composite current collector has a different structure compared with the traditional current collector. It adopts a "sandwich" structure, with the middle layer being a polymer substrate and a metal layer covering it. This structure has obvious advantages, and can use an extremely thin metal layer to achieve the conductivity of the current collector, thereby greatly reducing the amount of metal used.

[0004] In addition, the composite current collector performs well in terms of safety. Due to its thin metal layer, the burr size of the copper foil is small, and the polymer material layer as an insulating material will produce a circuit-breaking effect, which reduces the possibility of piercing the diaphragm, effectively preventing the battery from spontaneously igniting and effectively preventing thermal runaway.

[0005] However, the existing composite current collectors also have some shortcomings. For example, the second metal layer is pure copper, and the surface of pure copper foil is easily oxidized to form copper oxide, which has high surface resistance and poor conductivity, which will lead to reduced electrochemical performance of the battery. In addition, most of the composite current collectors in the prior art use PET (polyethylene terephthalate), PP (polypropylene), PE (polyethylene) or PI (polyimide) as the intermediate substrate, which is still lacking in heat resistance and mechanical strength, which will lead to poor safety of the battery in terms of needle puncture. Summary of the invention

[0006] Based on the technical problems existing in the background technology, the present invention proposes a composite current collector for a negative electrode of a lithium ion secondary battery, a preparation method and an apparatus thereof.

[0007] The present invention provides a composite current collector for a negative electrode of a lithium ion secondary battery. The configuration of the composite current collector for a negative electrode of a lithium ion secondary battery is:

[0008] Pour the conductive agent, the binder and the dispersant into a 200L V-type mixer and dry mix for 30-60 minutes, with the mass ratio of the three being (90-99): (0.3-3): (0.2-5), and mix to obtain a mixture;

[0009] The mixture is transferred to a 600L slurry mixing tank, and the solvent water is evenly added three times. After each water addition, the speed of the stirring paddle is controlled at 10-40r / min, the speed of the dispersion disk is controlled at 50m-100m / s, and the running time is 30-60min to obtain a conductive slurry with a solid content of 3-15%;

[0010] The conductive agent is one or more of acetylene black, carbon black, VGCF, carbon nanotubes, and graphene;

[0011] The binder is one or two of CMC sodium carboxymethyl cellulose and PAA;

[0012] The dispersant is one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium lignin sulfonate and sodium polystyrene sulfonate; poly(p-phenylene terephthalamide) (Kevlar) is electrostatically spun to form an aramid fiber aggregate, and the porosity is controlled at 10-90%; a layer of conductive carbon aqueous slurry is coated on the upper and lower surfaces of the poly(p-phenylene terephthalamide) (Kevlar) fiber aggregate; after the slurry is dried, it is subjected to a pressure molding process to form a composite current collector; the composite current collector is used as a negative electrode current collector of a lithium ion secondary battery, thereby improving the battery energy density; reducing the battery internal resistance, improving the battery rate performance and cycle life; improving the battery safety performance; the battery cell prepared by using the composite current collector prepared by the invention as the negative electrode current collector of a lithium ion secondary battery has a battery energy density improved by 3-8% compared with a traditional battery cell; the battery internal resistance is reduced by 5-12%, the battery cycle life is improved; and the battery safety performance is improved.

[0013] Preferably, in the melt spinning device inside the fiber weaving chamber, the melt spinning temperature of polyparaphenylene terephthalamide is set in the range of 450-520°C, the diameter of the spinning fiber is between 0.2-0.5μm, the spinning speed is 1-10 m / min, and the fibers flowing out of the melt spinning device are processed by the transfer shaft and the fiber aggregate collecting curtain under the action of electrostatic electricity, adsorption and their own temperature in the electrostatic adsorption device to form a fiber aggregate with a porosity of 1-90%. The electrostatic swing voltage is 20-50KV, and the adsorption wind size is -0.05MPa to -0.1MPa, which is convenient for processing.

[0014] Preferably, in the carbon layer coating area, the slurry is coated on the fiber aggregate in a micro-gravure coater, the residual material is collected in a collecting tank, the thickness of the single-layer wet film is controlled at 3-10μm, the coating speed is 20-100m / min, and the drying equipment is used for drying. The drying temperature is 60-100℃, the drying time is 0.5-2min, and the thickness of the single-layer functional layer after drying is controlled at 0.2-5μm, and the tape speed is 10-20m / min, which is convenient for subsequent processing.

[0015] Preferably, the composite current collector obtained in the electrostatic adsorption device is rolled by a hot roller of a rolling device, the rolling pressure is 1-10 MPa, the temperature of the hot roller is 300-500° C., and the final composite current collector is obtained, and the winding shaft is used for winding.

[0016] Preferably, in the preparation of the 40135 lithium-ion secondary battery, the 40135 lithium-ion secondary battery includes a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator.

[0017] Preferably, the positive electrode plate is composed of four parts: a positive electrode active material, a conductive agent, a binder, and a current collector. The positive electrode active material is lithium iron phosphate or a ternary material or a lithium manganese oxide material or a lithium iron manganese phosphate material; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder is PVDF; and the current collector is aluminum foil, which increases the choice of materials.

[0018] Preferably, the negative electrode plate is composed of four parts: a negative electrode active material, a conductive agent, a binder, and a current collector. The negative electrode active material is a hard carbon material; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder is CMC and SBR; and the current collector is copper foil or a composite current collector.

[0019] Preferably, the diaphragm is one of polyethylene, polypropylene, polyvinylidene fluoride, and aramid.

[0020] Preferably, the electrolyte is composed of an organic solvent and an electrolyte lithium salt, the organic solvent can be one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether; the electrolyte sodium salt can be one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium difluorophosphate, and lithium perchlorate.

[0021] The beneficial effects of the present invention are:

[0022] Poly(p-phenylene terephthalamide) (Kevlar) is electrostatically spun into an aramid fiber aggregate, and the porosity is controlled at 10-90%. A layer of conductive carbon aqueous slurry is coated on the upper and lower surfaces of the poly(p-phenylene terephthalamide) (Kevlar) fiber aggregate, and after the slurry is dried, it is subjected to a pressure molding process to form a composite current collector. The composite current collector is used as a negative electrode current collector for a lithium-ion secondary battery, thereby improving the battery energy density; reducing the battery internal resistance, improving the battery rate performance and cycle life; and improving the battery safety performance. Compared with a traditional battery cell, a battery cell prepared by using the composite current collector prepared by the present invention as a negative electrode current collector for a lithium-ion secondary battery has a battery energy density improved by 3-8%, a battery internal resistance reduced by 5-12%, and a battery cycle life improved; and improving the battery safety performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 The present invention provides a schematic diagram of the production of a composite current collector for a negative electrode of a lithium-ion secondary battery and a preparation method thereof.

[0024] In the figure: 1. melt spinning device; 2. transfer shaft; 3. electrostatic adsorption device; 4. fiber aggregate collection curtain; 5. fiber aggregate; 6. collection tank; 7. micro-gravure coater; 8. carbon layer coating area; 9. drying equipment; 10. rolling equipment; 11. winding shaft. DETAILED DESCRIPTION

[0025] The present invention will be further explained below in conjunction with specific embodiments.

[0026] Example

[0027] refer to Figure 1 In this embodiment, a composite current collector for a negative electrode of a lithium-ion secondary battery is proposed. The configuration of the composite current collector for a negative electrode of a lithium-ion secondary battery is:

[0028] Pour the conductive agent, the binder and the dispersant into a 200L V-type mixer and dry mix for 30-60 minutes, with the mass ratio of the three being (90-99): (0.3-3): (0.2-5), and mix to obtain a mixture;

[0029] The mixture is transferred to a 600L slurry mixing tank, and the solvent water is evenly added three times. After each water addition, the speed of the stirring paddle is controlled at 10-40r / min, the speed of the dispersion disk is controlled at 50m-100m / s, and the running time is 30-60min to obtain a conductive slurry with a solid content of 3-15%;

[0030] The conductive agent is one or more of acetylene black, carbon black, VGCF, carbon nanotubes, and graphene;

[0031] The binder is one or two of CMC sodium carboxymethyl cellulose and PAA;

[0032] The dispersant is one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium lignin sulfonate and sodium polystyrene sulfonate; poly(p-phenylene terephthalamide) (Kevlar) is electrostatically spun to form an aramid fiber aggregate, and the porosity is controlled at 10-90%; a layer of conductive carbon aqueous slurry is coated on the upper and lower surfaces of the poly(p-phenylene terephthalamide) (Kevlar) fiber aggregate; after the slurry is dried, it is subjected to a pressure molding process to form a composite current collector; the composite current collector is used as a negative electrode current collector of a lithium ion secondary battery, thereby improving the battery energy density; reducing the battery internal resistance, improving the battery rate performance and cycle life; improving the battery safety performance; the battery cell prepared by using the composite current collector prepared by the invention as the negative electrode current collector of a lithium ion secondary battery has a battery energy density improved by 3-8% compared with a traditional battery cell; the battery internal resistance is reduced by 5-12%, the battery cycle life is improved; and the battery safety performance is improved.

[0033] Embodiment 1

[0034] S1: Configuration of conductive slurry: dry mix the conductive agent, binder and dispersant with a total weight of 20 kg in a 200L V-type mixer for 50 minutes, and the mass ratio of the three is 98:1.5:0.5; transfer the mixture to a 600L slurry mixing tank, and add the organic solvent evenly in three times. After each addition of water, the stirring paddle speed is 30r / min, the dispersion disk linear speed is 75m / s, and the running time is 60min; obtain a conductive slurry with a solid content of 10%; the conductive agent is acetylene black and graphene, and the mass ratio of the two is 7:3; the binder is CMC; the dispersant is polyvinyl pyrrolidone;

[0035] S2: Fiber weaving room: In the melt spinning device, the melt spinning temperature of polyparaphenylene terephthalamide is set in the range of 500°C, the diameter of the spinning fiber is between 0.2-0.5μm, and the spinning speed is 5 m / min; the fibers flowing out of the melt spinning device are subjected to the electrostatic action, adsorption action and self-temperature action in the electrostatic adsorption device to form fiber aggregates with a porosity of 25%, the electrostatic swing voltage is 25KV, and the adsorption wind size is -0.06MPa to -0.1MPa; the thickness of the fiber aggregate is 4.5μm.

[0036] S3: The slurry is coated on the fiber aggregate in a micro-gravure coater to obtain a composite foil, and the thickness of the single-layer wet film is controlled at 10 μm; the coating speed is 10 m / min, the drying temperature is 80°C, and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled to be 1.5 μm;

[0037] S4: rolling the composite current collector obtained in the electrostatic adsorption device with a hot roller at a rolling pressure of 2 MPa; the temperature of the hot roller is 350° C. to obtain a final composite current collector with a thickness of 6.0 μm.

[0038] Embodiment 2

[0039] S1: Configuration of conductive slurry: dry mix the conductive agent, binder and dispersant with a total weight of 30 kg in a 200L V-type mixer for 50 minutes, and the mass ratio of the three is 98.5:1.0:0.5; transfer the mixture to a 600L slurry mixing tank, and add the organic solvent evenly in three times. After each addition of water, the stirring paddle speed is 40r / min, the dispersion disk linear speed is 80m / s, and the running time is 60min; obtain a conductive slurry with a solid content of 8%; the conductive agent is acetylene black and carbon nanotubes, and the mass ratio of the two is 2:8; the binder is CMC; the dispersant is polyvinyl pyrrolidone;

[0040] S2: Fiber weaving room: In the melt spinning device, the melt spinning temperature of polyparaphenylene terephthalamide is set in the range of 480°C, the diameter of the spinning fiber is between 0.2-0.4μm, and the spinning speed is 6 m / min; the fibers flowing out of the melt spinning device are subjected to the electrostatic action, adsorption action and self-temperature action in the electrostatic adsorption device to form fiber aggregates with a porosity of 35%, the electrostatic swing voltage is 35KV, and the adsorption wind size is -0.08MPa; the thickness of the fiber aggregate is 5.1μm.

[0041] S3: The slurry is coated on the fiber aggregate in a micro-gravure coater to obtain a composite foil, and the thickness of a single layer of wet film is controlled at 8 μm; the coating speed is 10 m / min, the drying temperature is 80°C, and the drying time is 2 min; after drying, the thickness of a single functional layer is controlled to be 1.2 μm;

[0042] S4: The composite current collector obtained in the electrostatic adsorption device is rolled by a hot roller with a rolling pressure of 5 MPa; the temperature of the hot roller is 360° C. to obtain a final composite current collector with a thickness of 6 μm.

[0043] Embodiment 3

[0044] S1: Configuration of conductive slurry: dry mix the conductive agent, binder and dispersant with a total weight of 25 kg in a 200L V-type mixer for 60 minutes, and the mass ratio of the three is 95.5:2.0:2.5; transfer the mixture to a 600L slurry mixing tank, and add the organic solvent evenly in three times. After each addition of water, the stirring paddle speed is 60r / min, the dispersion disk linear speed is 90m / s, and the running time is 60min; obtain a conductive slurry with a solid content of 6%; the conductive agent is graphene and carbon nanotubes, and the mass ratio of the two is 5:5; the binder is CMC; the dispersant is sodium polyacrylate;

[0045] S2: Fiber weaving room: In the melt spinning device, the melt spinning temperature of poly(p-phenylene terephthalamide) is set in the range of 520°C, the diameter of the spinning fiber is between 0.2-0.3μm, and the spinning speed is 8m / min; the fibers flowing out of the melt spinning device are subjected to the electrostatic action, adsorption action and self-temperature action in the electrostatic adsorption device to form a fiber aggregate with a porosity of 25%, the electrostatic swing voltage is 40KV, and the adsorption wind size is -0.09MPa;

[0046] S3: The slurry is coated on the fiber aggregate in a micro-gravure coater to obtain a composite foil 1, and the single-layer wet film thickness is controlled at 9 μm; the coating speed is 10 m / min, the drying temperature is 90°C, and the drying time is 2 min; after drying, the thickness of the single-layer functional layer is controlled at 1.4 μm; the thickness of the fiber aggregate is 4.0 μm.

[0047] S4: The composite current collector obtained in the electrostatic adsorption device is rolled by a hot roller with a rolling pressure of 1 MPa; the temperature of the hot roller is 400° C. to obtain a final composite current collector with a thickness of 6 μm.

[0048] Comparative Example 1

[0049] Use 6μm thick copper foil.

[0050] The 40135-30Ah cylindrical lithium ion battery of Examples 1-3 and Comparative Example 1 was prepared according to the following method

[0051] S1: Preparation of positive electrode

[0052] 96% NCM811 ternary material, 2% acetylene black, 2% PVDF, add NMP, disperse evenly to prepare positive electrode slurry, evenly coat the positive electrode slurry on the surface of aluminum foil, roll and cut after drying to obtain negative electrode;

[0053] S2: Preparation of negative electrode sheet

[0054] 95.5% graphite, 1% acetylene black, 1.5% CMC, and 2% SBR are added to purified water and dispersed evenly to prepare negative electrode slurry, and the negative electrode slurry is evenly coated on the surface of the copper foil of Examples 1-3 and Comparative Example 1, and rolled and cut after drying to obtain a negative electrode;

[0055] S3: Diaphragm

[0056] The diaphragm is made of polyethylene (PE) porous polymer film.

[0057] S4: Preparation of electrolyte

[0058] 16g of lithium hexafluorophosphate, 25g of ethylene carbonate, 58g of dimethyl carbonate, and 1g of methyl methylthiosulfonate are mixed evenly to prepare an electrolyte.

[0059] The positive electrode sheet, the separator and the negative electrode sheet are wound into an electrode group, and a 40135-30Ah cylindrical lithium-ion battery is assembled after groove rolling, liquid injection and sealing.

[0060] Cycle life test method: At 25°C, the batteries prepared in the examples and comparative examples were charged to 4.2V at a rate of 0.5C and discharged to 2V at a rate of 0.5C. Full charge and discharge cycle tests were performed until the capacity of the battery was less than 80% of the initial capacity, and the number of cycles was recorded.

[0061] Puncture test: Fix the fully charged battery cell firmly on the puncture workbench. You can use tools such as tape and clamps to ensure that the battery does not move or shake during the puncture process. Set the steel needle on the puncture test machine to a 5mm diameter, a cone angle of 45°, and a puncture speed of (25±5)mm / s. Start the puncture device to make the steel needle penetrate the battery at a set speed perpendicular to the direction of the battery plate. The steel needle stays in the battery and maintains the puncture state. After the steel needle punctures the battery, observe it for 1 hour to see if the battery has any smoke, fire, explosion, etc.

[0062] Energy density: battery capacity*voltage / battery weight.

[0063] As can be seen from the table below, the 40135 ternary cylindrical lithium battery prepared using the composite current collector of this patent has improved energy density and significantly improved cycle life compared to lithium batteries prepared using ordinary copper foil; especially in terms of safety, the needle puncture pass rate is 100%.

[0064] Energy density (Wh / kg) Cycle life (times) acupuncture Embodiment 1 261 3188 No smoke, no fire, no explosion Embodiment 2 258 3216 No smoke, no fire, no explosion Embodiment 2 259 3367 No smoke, no fire, no explosion Comparative Example 1 253 2763 explode

[0065] The above description is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.

Claims

1. A composite current collector for a negative electrode of a lithium ion secondary battery, characterized in that: Configuration of the composite current collector for the negative electrode of the lithium ion secondary battery: Pour the conductive agent, the binder and the dispersant into a 200L V-type mixer and dry mix for 30-60 minutes. The mass ratio of the three is (90-99): (0.3-3): (0.2-5), and mix to obtain a mixture; The mixture was transferred to a 600L slurry mixing tank, and the solvent water was evenly added three times. After each addition of water, the speed of the stirring paddle was controlled at 10-40r / min, the speed of the dispersion disk was controlled at 50m-100m / s, and the running time was 30-60min to obtain a conductive slurry with a solid content of 3-15%; The conductive agent is one or more of acetylene black, carbon black, VGCF, carbon nanotubes, and graphene; The binder is one or two of CMC sodium carboxymethyl cellulose and PAA; The dispersant is one or more of polyvinyl pyrrolidone, sodium polyacrylate, sodium lignin sulfonate and sodium polystyrene sulfonate.

2. The method for preparing a composite current collector for a negative electrode of a lithium ion secondary battery according to claim 1, characterized in that: In the melt spinning device (1) inside the fiber weaving chamber, the melt spinning temperature of poly(p-phenylene terephthalamide) is set in the range of 450-520°C, the diameter of the spinning fiber is between 0.2-0.5 μm, and the spinning speed is 1-10 m / min. The fibers flowing out of the melt spinning device (1) are treated by the transfer shaft (2) and the fiber aggregate collecting curtain (4) under the action of electrostatic action, adsorption action and self-temperature in the electrostatic adsorption device (3) to form a fiber aggregate (5) with a porosity of 1-90%. The electrostatic swing voltage is 20-50 KV, and the adsorption wind size is -0.05 MPa to -0.1 MPa.

3. The method for preparing a composite current collector for a negative electrode of a lithium ion secondary battery according to claim 2, characterized in that: In the carbon layer coating area (8), the slurry is coated on the fiber aggregate (5) in a micro-gravure coater (7), and the residual material is collected in a collecting tank (6). The thickness of the single-layer wet film is controlled at 3-10 μm, the coating speed is 20-100 m / min, and the slurry is dried using a drying device (9). The drying temperature is 60-100° C. and the drying time is 0.5-2 min. After drying, the thickness of the single-layer functional layer is controlled at 0.2-5 μm, and the conveying speed is 10-20 m / min.

4. The method for preparing a composite current collector for a negative electrode of a lithium ion secondary battery according to claim 3, characterized in that: The composite current collector obtained in the electrostatic adsorption device (3) is rolled by a hot roller of a roller pressing device (10) at a rolling pressure of 1-10 MPa and a hot roller temperature of 300-500° C. to obtain a final composite current collector, which is then rolled up by a winding shaft (11).

5. A battery with a composite current collector for a negative electrode of a lithium-ion secondary battery according to claim 1, characterized in that: The preparation of the 40135 lithium-ion secondary battery, the 40135 lithium-ion secondary battery includes a positive electrode plate, a negative electrode plate, an electrolyte and a separator.

6. A battery with a composite current collector for a negative electrode of a lithium-ion secondary battery according to claim 5, characterized in that: The positive electrode plate is composed of four parts: positive electrode active material, conductive agent, binder, and current collector. The positive electrode active material is lithium iron phosphate or ternary material or lithium manganese oxide material or lithium iron manganese phosphate material; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder is PVDF; and the current collector is aluminum foil.

7. A battery with a composite current collector for a negative electrode of a lithium-ion secondary battery according to claim 5, characterized in that: The negative electrode sheet is composed of four parts: negative electrode active material, conductive agent, binder, and current collector. The negative electrode active material is hard carbon material; the conductive agent can be one or more of acetylene black, carbon black, carbon nanotubes, and graphene; the binder is CMC and SBR; the current collector is copper foil or a composite current collector.

8. A battery with a composite current collector for a negative electrode of a lithium-ion secondary battery according to claim 5, characterized in that: The diaphragm is one of polyethylene, polypropylene, polyvinylidene fluoride, and aramid.

9. A battery with a composite current collector for a negative electrode of a lithium-ion secondary battery according to claim 5, characterized in that: The electrolyte is composed of an organic solvent and an electrolyte lithium salt. The organic solvent can be one or more of ethylene carbonate, propylene carbonate, diethyl carbonate, dimethyl carbonate, ethyl methyl carbonate, propylene carbonate, methyl acetate, ethyl propionate, fluoroethylene carbonate, ethyl ether, diethylene glycol dimethyl ether, triethylene glycol dimethyl ether, tetraethylene glycol dimethyl ether, and methyl tert-butyl ether; the electrolyte sodium salt can be one or more of lithium hexafluorophosphate, lithium bis(fluorosulfonyl imide), lithium bis(trifluoromethanesulfonyl imide), lithium trifluoromethanesulfonate, lithium tetrafluoroborate, lithium difluorophosphate, and lithium perchlorate.